2016
DOI: 10.5492/wjccm.v5.i2.111
|View full text |Cite
|
Sign up to set email alerts
|

Association between infections caused by multidrug-resistant gram-negative bacteria and mortality in critically ill patients

Abstract: The incidence of gram-negative multidrug-resistant (MDR) bacterial pathogens is increasing in hospitals and particularly in the intensive care unit (ICU) setting. The clinical consequences of infections caused by MDR pathogens remain controversial. The purpose of this review is to summarize the available data concerning the impact of these infections on mortality in ICU patients. Twenty-four studies, conducted exclusively in ICU patients, were identified through PubMed search over the years 2000-2015. Bloodst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 73 publications
2
37
0
4
Order By: Relevance
“…Studies have also shown an increasing carbapenem-resistance in P. aeruginosa isolates from ICU-acquired infections [19][20][21]. In our study, there was a significantly decrease in the resistant rates of Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 72%
“…Studies have also shown an increasing carbapenem-resistance in P. aeruginosa isolates from ICU-acquired infections [19][20][21]. In our study, there was a significantly decrease in the resistant rates of Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 72%
“…There is a remarkable increase of multidrug-resistant (MDR) gram-negative bacteria in hospitals and significantly in the intensive care unit (ICU) setting. The clinical outcomes of infections brought about by MDR pathogens as yet dubious 14 . The resistance pattern is most likely noted in ICUs due to the unlimited use of antibiotics in these units compared to the other hospital departments 15 and 70% of these infections were caused by GNB 16 .…”
Section: Discussionmentioning
confidence: 99%
“…(3032) This finding is concerning because antibiotic-resistant infections are associated with increased morbidity and mortality, as well as longer and more expensive hospital stays. (9, 33) SAP is commonly used for procedures with relatively low risks for post-operative infection. If SAP is associated with even a slight increase in risk for post-operative antibiotic-resistant infections, this observation would become a significant factor in the risk-benefit equation for use of SAP.…”
Section: Discussionmentioning
confidence: 99%